Pictionaire: Supporting Collaborative Design Work by Integrating Physical and Digital Artifacts - Hartmann, Björn; Morris, Meredith Ringel; Benko, Hrvoje; Wilson, Andy (CSCW '10 Proceedings of the 2010 ACM conference on Computer supported cooperative work, 2010)
This paper introduces an interactive tabletop system that enhances creative collaboration across physical and digital artifacts. Pictionaire offers capture, retrieval, annotation, and collection of visual material. It enables multiple designers to fluidly move imagery from the physical to the digital realm; work with found, drawn and captured imagery; organize items into functional collections; and record meeting histories. These benefits are made possible by a large interactive table augmented with high-resolution overhead image capture. Summative evaluations with 16 professionals and four student pairs validated discoverability and utility of interactions, uncovered emergent functionality, and suggested opportunities for transitioning content to and from the table.